Keys to eukaryality: planctomycetes and ancestral evolution of cellular complexity - Fuerst, John A.; Sagulenko, Evgeny (Frontiers in Microbiology, 2012)
Planctomycetes are known to display compartmentalization via internal membranes, thus resembling eukaryotes. Significantly, the planctomycete Gemmata obscuriglobus has not only a nuclear region surrounded by a double-membrane, but is also capable of protein uptake via endocytosis. In order to clearly analyse implications for homology of their characters with eukaryotes, a correct understanding of planctomycete structure is an essential starting point. Here we outline the major features of such structure necessary for assessing the case for or against homology with eukaryote cell complexity. We consider an evolutionary model for cell organization involving reductive evolution of planctomycetes from a complex protoeukaryote-like LUCA ancestor, and evaluate alternative models for origins of the unique planctomycete cell plan. Overall, the structural and molecular evidence is not consistent with convergent evolution of eukaryote-like features in a bacterium and favours a homologous relationship of planctomycetes and eukaryotes